EXAMINATION OF THE EXTENT TO WHICH ADOLESCENT REPRODUCTIVE HEALTH SERVICES ARE APPROPRIATE, ACCESSIBLE AND USER FRIENDLY - Mbatia, Prof. Paul; Wahome, Mercy (Global Journal of Health Sciences, 2017)
Purpose: The objective of the study was to examine the extent to which adolescent reproductive health services are appropriate, accessible and user friendly. Methodology: A cross-sectional survey research design was adopted for this study to to examine the extent to which adolescent reproductive health services are appropriate, accessible and user friendly. The survey targeted youth aged between 10 - 25 years and was used to capture their perceptions on the youth-friendliness of the facilities they attended. Through the survey the researcher generated quantitative data. In addition, field research was used to supplement the survey and generate qualitative data. The selected UNFPA trained clinics for the research included: Casino, Woodley, Langata, Kangemi and Dandora Health Clinics. The clinics with untrained health providers for the research included: Ngaira, Makadara, Riruta, Umoja and Westlands Health Clinics. Qualitative data generated from the key informants, was analysed by noting themes that emerged from their opinions. Results: The youth consider provision of recreational facilities as an important component in the constitution of a youth friendly service. These facilities attract the youth to a health facility thus creating an opportunity to educate them on reproductive health among other prevention services. Thus, the need invest in recreational facilities. Unique contribution to theory, practice and policy: Health facilities under NCC need to examine their health provision system to ensure that the facilities attract both male and female youth, and that young men can access RH services without feeling out of place. This would require separating formal reproductive health services from MCH/FP services.